Night watch : poems - Young, Kevin, 1970- (Alfred A. Knopf, 2025)
"Following on his exquisite Stones, Young's new collection shapes stories of familial and familiar love, inspired in part by other lives. A central sequence, "The Two-Headed Nightingale," is spoken by Millie-Christine McCoy, the famous conjoined African American "Carolina Twins." Born into slavery and ill treatment as a "freak" sensation in 1851 and later free women, their alto and soprano voices harmonized, and Young's poem explores their evolving selfhood and self-understanding: "As one we sang, /we spake- / She was the body / I the soul / Without one / Perishes the whole." In "Darkling," a cycle of poems written in reaction to Robert Rauschenberg's paintings made while listening to Dante's Inferno canto by canto, Young expands and embroiders the circles of Hell, incorporating his own experiences, drawing a cosmology of both loneliness and accompaniment, making space for the communal and singular voicing of both sorrow and hope, spiced with rueful notes on the failures of American culture. When he goes, he warns, don't sing "Amazing Grace"-not that "National / Anthem of Suffering." No, he suggests, "When I Fly Away, / Don't dare hold no vigil . . . Just burn the whole / Town on down.""--